P-568 The effect of recombinant hCG on FSH-induced ovarian stimulation in rats depends on the FSH dose and can be detrimental at high concentrations. (30th June 2022) - Schoeller, E; Jespersen, S; La, E; Ramirez, J; Hong, D; Rives, M.L; Mannaerts, B
Abstract: Study question: What is the effect of choriogonadotropin beta (CG beta) on FSH-induced ovarian stimulation and multifollicular development in a rat model? Summary answer: CG beta dose-dependently potentiates effects of low-to-mid FSH doses but has inhibitory effects at high concentrations: optimal CG beta/FSH ratio depends on the FSH dose. What is known already: Similarly to follitropin delta (rFSH), CG beta (FE 999302) is a novel recombinant hCG purified from the human PER.C6®cell line. A recent placebo-controlled trial in women undergoing ovarian stimulation with follitropin delta demonstrated that the addition of 1 to 12 µg CG beta reduced the number of intermediate follicles and related hormones. This observation required further preclinical research to (1) evaluate whether the pharmacology of CG beta at LH/CGR was different than other hCG forms used in the clinic and/or (2) assess the effect of high concentrations of hCG and different hCG/FSH ratios on multiple follicular development and follicle atresia. Study design, size, duration: Signaling properties of CG beta and other LH/hCG forms were compared at downstream pathways of LH/CGR in recombinant systems and human granulosa cells. To evaluate the effects of FSH±hCG in vivo, juvenile female rats were injected subcutaneously twice daily with follitropin delta ± CG beta/alfa for three days followed by an ovulatory dose of hCG. Oviducts were then collected for oocyte enumeration, ovaries and uteri were weighed, and ovaries were fixed for histological analysis. Participants/materials, setting, methods: The pharmacology of CG beta and other LH/hCG forms was evaluated in a cAMP assay in human granulosa cells from follicular fluid from IVF patients and in recombinant systems, at the Gs, Gq and arrestin pathways. In the rat model, a dose response of follitropin delta (Rekovelle) was first evaluated, followed by evaluation of the dose-dependent effects of CG beta (0.00117-2.4 µg/kg), or CG alfa (Ovidrel/Ovitrelle), in combination with 1, 3 or 10 µg/kg rFSH. Main results and the role of chance: The in vitro pharmacology (potency and efficacy) of CG beta was similar to recombinant LH, urinary hCG and recombinant hCG (CG alfa) tested at all proximal pathways evaluated downstream of LH/CGR as well as in human granulosa cells. In vivo, treatment with follitropin delta induced a bell-shaped dose-response curve for oocyte release with a maximum response of 40-50 oocytes at 8-10 µg/kg follitropin delta dose. The addition of CG beta dose-dependently potentiated the effects at low-to-mid follitropin delta doses but had inhibitory effects on the number of ovulated oocytes at high CG beta concentrations. The lowest CG beta dose that clearly reduced the number of ovulated oocytes was 2.4, 0.6 and 0.3 µg/kg in combination with a fixed dose of 1, 3 and 10 µg/kg follitropin delta, respectively, which indicated that the optimal hCG/FSH ratio and corresponding hCG efficacious dose was inversely related to the FSH dose. There was no difference between CG beta and CG alfa for the dose effect on the number of ovulated oocytes or ovarian weight. Histology data indicated many cystic follicles following high CG beta exposure which may represent atretic follicles prior to triggering follicular maturation and ovulation. Limitations, reasons for caution: This is the first study demonstrating that the FSH dose in combination with the hCG dose determines the effect on multiple follicle growth, ovulation, and atresia. These observations need to be confirmed in clinical research, as doses and ratios applied in the rat cannot be extrapolated to the clinical setting. Wider implications of the findings: A better understanding of the effect of different FSH to hCG ratios will help to improve current mixed protocols and design future recombinant combination products providing the optimal treatment outcome for each individual patient. Trial registration number: not applicable